Characterization of Organic Fraction Produced by Spirulina platensis in Oxidation Ditch Reactor - Fairuz Khurotul Aini; Valentino Rizkiar Pradana; Euis Nurul Hidayah; Okik Hendriyanto Cahyonugroho (Future Science)
The biggest source of river water pollution is domestic wastewater, about 60-70% with 6.1% treatment and 40% of the pollution comes from industry or others and is exacerbated by the uncontrolled algae growth. The diversity of algal organic matter (AOM) in domestic wastewater causes several problems in water treatment. Fluorescence Excitation Emission Matrix (FEEM) has been widely used to determine the structural and compositional characteristics of molecules. The purpose of this study was to determine the characteristics of the AOM fraction produced by the microalgae Spirulina platensis using FEEM. The peak percentage of EEM and the Fluorescence Regional Index (FRI) was used to represent the substance contained in the sample. The results showed the microalgae Spirulina platensis identified as containing fraction aromatic protein-like, fulvic acid-like, soluble microbial product-like, and humic acid-like where the percentage of FRI of each fraction fluctuates due to internal factors such as microbial carbon sources and external factors such as temperature and oxygen supply.